SYSTEMATIC LITERATURE REVIEW ON WOMEN ENTREPRENEURS IN ACCOUNTING (2022-2024) (REMUNOM, 2025)
This research proposes a systematic review of the literature on the role of women entrepreneurs in accounting, focusing on academic publications published between 2022 and 2024. Despite the growth in female presence in the sector, challenges such as restricted access to credit, gender bias, and difficulties in balancing personal and professional life persist. The study seeks to answer the main aspects involved in this activity and how they impact business success and sustainability. The overall objective is to identify these aspects in recent research, describing the main points covered and analyzing social and cultural factors that influence the context of these entrepreneurs. Methodologically, this is a qualitative, exploratory study, using bibliographic research and a systematic literature review. The analysis of the articles revealed patterns such as the pursuit of autonomy and overcoming gender barriers as the main motivations, while specialization in niches, the use of technology, and support networks emerge as successful strategies. The identified gaps point to the need for more longitudinal research, quantitative studies with representative samples, and international comparative analyses. The results are expected to contribute to academic debate and encourage policies and practices that support female entrepreneurship in accounting.